ISU-ISU KEAMANAN CLOUD COMPUTING - Ali Ahmadi (STMIK Mardira Indonesia, Bandung, 2015)
Cloud computing is an alternative model of the implementation and utilization of services related to Information Technology. This paradigm is touted to simplify the way procurement and purchasing IT products by the buyer, and also lighten the load shipments by vendor. However, there are a number of risks and constraints to adopt this model. Security is always associated the word with cloud computing. Some sources of security issues in the cloud is determined by its own cloud -based infrastructure network (internet). The basic concept of distributed computing cloud that contains the potential security vulnerabilities continues to be the study of the experts. The reason is distributed in cloud computing relies heavily on Internet technology. In this paper will try for reviews safety aspects related to the infrastructure and the implementation of cloud computing it. Keywords: Cloud Computing, Security Abstrak Cloud computing adalah suatu alternatif model penyelenggaraan dan pemanfaatan layanan-layanan terkait Teknologi Informasi. Paradigma ini disebut-sebut dapat mempermudah cara pengadaan dan pembelian produk-produk IT oleh pembeli, serta memperingan pula beban pengiriman oleh vendor. Bagaimanapun juga, terdapat sejumlah resiko dan kendala untuk mengadopsi model ini. Security (keamanan) adalah kata yang selalu dikaitkan orang dengan cloud computing. Beberapa sumber masalah keamanan dalam cloud ditentukan oleh infrastruktur cloud sendiri yang berbasis jaringan (internet). Konsep dasar cloud yaitu distributed computing mengandung potensi kerawanan keamanan yang terus menerus menjadi kajian para ahli. Sebabnya adalah distributed computing dalam cloud sangat bergantung pada teknologi internet. Dalam paper ini akan coba diulas aspek-aspek keamanan terkait dengan infrastruktur maupun implementasi dari cloud computing itu sendiri. Kata kunci: Cloud Computing, Security, Keamanan